ANALISIS SISTEM KLAIM JAMINAN HARI TUA (JHT) PADA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN CABANG CILACAP - Lestari, Indah; Hirawati, Heni (JAB (Jurnal Akuntansi & Bisnis), 2021)
Old Age Security is one of the government programs organized by BPJS Employment. The purpose of this study was to find out how the Old Age Security claim system at BPJS Employment Cilacap Branch is and to identify the obstacles that may happened. The object of this research is all participants who claim Old Age Security at BPJS Employment Cilacap Branch. The research method used in this study is a qualitative research method in the form of interviews with archiving staff and observations at the BPJS Employment Office. The results of this study indicate that the claim system in BPJS Employment Cilacap is quite good, this can be seen from the rate of increase every year. There are three ways to claim system, namely manual, online, and onsite. The obstacles that exist in the Old Age Security claim system at BPJS Employment Cilacap are a poor filing system and participants who lack technology.Â Keywords: BPJS Employment, Claims, Old Age Security, System